Effectiveness of an Educational Program upon Nurses’ Knowledge about Complications Reduction at the Peritoneal Dialysis Units - Dergham M. Hameed (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The study aims at identifying the nurses’ knowledge about peritoneal dialysis complications, toconstruct an education program for nurses in peritoneal dialysis units, to determine the effectiveness of theeducation program upon the nurses' knowledge about complications of peritoneal dialysis, and to identify therelationship between the nurses’ knowledge and their demographic characteristics of level of education andyears of experience.Methodology: A quasi-experimentai study was carried out at the peritoneal dialysis units of Baghdad teachinghospitals, from April 2004 to April 2006.٨ purposive sample of (50) nurse was selected from Baghdad teaching hospitals. These nurses working at theperitoneal dialysis units to provide nursing care for a patient who has undergone peritoneal dialysis.The data were collected through the use of constructed questionnaire, which comprised of (56) item distributedin (7)sections.The reliability of the instrument was determined through test-retest and the validity through a panel study ofexperts.The data were analyzed through the application of descriptive statistical analysis that included (frequency,mean, mean of scores, standard deviation, and percentage) and the application of inferential statistical analysisthat included (test for independent sample, test for dependent sample pre-test and post-test, pearsoncorrelation coefficient, Chi-square, and analysis of variance for the difference between pre-test, post-testi, andpost-test2 of the study group).Results: The results of the study indicated that the education program had a positive impact on the knowledgeof nurses in peritoneal dialysis units regarding peritoneal dialysis complications and significant association wasidentified between the nurses' knowledge relation to their education level at the study group (pre-test).Recommendations: Based on the result of the study, the study recommended that Nurses who are working atthe peritoneal dialysis unit should be encouraged to participate in education program and training session fortheir benefit of their practice in such units, in service continuing education program should be presented tonurse at the peritoneal dialysis unit on a regular base to maintain their level of knowledge.